Quantifying food losses in the beans value chain in Rwanda: Analysis and results from a baseline survey - Delgado, Luciana; Niyonsingiza, Josue; Bachewe, Fantu Nisrane (International Food Policy Research Institute, 2024)
At the global level, awareness about the significance of food loss and waste has grown significantly over the past decade. The international community has taken the matter to hand as part of the 2030 Agenda for Sustainable Development and has committed to “halve the per capita global food waste at the retail and consumer level and reduce food losses along production and supply chains, including post-harvest losses” by 2030.